2015
DOI: 10.1007/s00784-015-1540-2
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A and IL-17F polymorphisms in rheumatoid arthritis and Sjögren’s syndrome

Abstract: A better understanding of the pathogenesis of SS is demanded to an adequate treatment as well as to the development of new management strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…This result confirmed a previous report in the Tunisian population [ 26 ]. Again, most of published studies performed in Algerian [ 27 ], Polish [ 28 , 29 ], Brazilian [ 30 ] and Chinese [ 31 ] populations emphasized the lack of association between the IL-17A rs2275913 and RA risk. Nevertheless, two studies performed in Norwegian [ 32 ] and Brazilian [ 33 ] reported that the rs2275913 polymorphism increased risk of RA.…”
Section: Discussionmentioning
confidence: 99%
“…This result confirmed a previous report in the Tunisian population [ 26 ]. Again, most of published studies performed in Algerian [ 27 ], Polish [ 28 , 29 ], Brazilian [ 30 ] and Chinese [ 31 ] populations emphasized the lack of association between the IL-17A rs2275913 and RA risk. Nevertheless, two studies performed in Norwegian [ 32 ] and Brazilian [ 33 ] reported that the rs2275913 polymorphism increased risk of RA.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed the controls of each study for the fitness in the HWE. The study of Carvalho et al 17 was deviated from HWE. In addition, the HWE of Louahchi et al 19 was not available for the lack of genotype frequency data.…”
Section: Resultsmentioning
confidence: 90%
“…Finally, seven studies including 1,409 RA patients and 1,303 controls were eligible for the present study. [13][14][15][16][17][18][19] The flow chart of the literature research and study selection is shown in Figure 1. Among the included studies, all seven investigated the correlation between 7488A/G and RA susceptibility, but only four (containing 1,093 cases and 969 controls) researched 7383A/G and RA risk.…”
Section: Resultsmentioning
confidence: 99%
“…Although there is a clear pattern of Th17 response in inflammatory and autoimmune diseases, the relevance of IL17 polymorphism varies according to the disease. We have previously demonstrated a lack of association between IL17A SNP, rheumatoid arthritis and secondary Sjögren's syndrome (Carvalho et al., ) in a study with 206 individuals, but a weak association was demonstrated in a larger sample (Nordang et al., ). In ankylosing spondylitis, a SNP in the promoter region of IL17RA was associated with an elevated risk, with a stronger association in individuals with severe forms (Vidal‐Castiñeira et al., ).…”
Section: Discussionmentioning
confidence: 87%